1983
DOI: 10.1111/j.1600-0773.1983.tb02692.x
|View full text |Cite
|
Sign up to set email alerts
|

LD50 ‐ its value for the pharmaceutical industry in safety evaluation of drugs.

Abstract: Does the pharmaceutical industry perform LD50‐determinations in animals just because it is required by the authorities or are there any scientific benefits from counting dead animals and calculating and index of lethal toxicity? This is an important question when discussing LD50 and possible alternatives. We will try to answer this question by presenting data and some views collected during almost ten years at a Swedish pharmaceutical company. We will describe how we have made use of the LD50‐values in the saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The dose is used to calculate the initial dose to be tried in man during the clinical trials. It has been suggested that a simple limit test, aimed at determining the effect on animals, of the largest dose likely to be administered to a human being is often enough [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dose is used to calculate the initial dose to be tried in man during the clinical trials. It has been suggested that a simple limit test, aimed at determining the effect on animals, of the largest dose likely to be administered to a human being is often enough [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it does not cause p53 gene (tumour suppressor) mutation along with the inactive Heat shock response. The average lethal dosage (LD50) for 5BNA is predicted to be 3720 mg/kg and it lies in the toxicity class of Class VI which indicates that the compound is non-toxic in nature and can also be proposed as the drug [ 85 ].…”
Section: Resultsmentioning
confidence: 99%
“…The lethal dose (LD50) is amount required to kill 50% of test animals (usually rats or mice). LD50 < 25 mg/kg represents very toxic; LD50 < 25 mg/kg to 200 mg/kg is toxic; LD50 < 200 mg/kg to 2000 mg/kg < LD50 is harmful, while substances of LD50 > 2000 mg/kg are not classified as toxic agents [38]. Human beings have been using biological toxins since long.…”
Section: Role Of Bacterial Toxins In Biological Warfare or Bioterrorismmentioning
confidence: 99%